Attracting International Students: Experiences of Asian Countries and the Case of University of Social Sciences and Humanities, Vietnam National University-Ho Chi Minh - Khanh, Mai Thi Kim; Ngoc, Chau Huy (VNU Journal of Science: Education Research, 2021)
In recent years, internationalization of higher education has become a guiding agenda and a policy both at the Party and Government’s levels, and of which international student recruitment is seen as an important measure which could improve higher education institutions’ international orientation, contribute to reputation and international university rankings. Hence learning from countries which have successfully internationalized their higher educations in order to draw lessons for universities in Vietnam to utilize their existing advantages and remedy shortcomings in internationalization is a necessity. This article serves as an overview of experiences of Asian countries based on studies conducted in China, Taiwan, and Korea, which suggest that languages and distinctive cultural elements could be important factors attracting international students to these Asian destinations. University of Social Sciences and Humanites will then be presented as a Vietnamese higher education institution that could become a destination of foreign students using its distinctive strengths, namely Vietnamese language and Vietnamese Studies programs and cultural exchange activities.